Cholesterol Levels After Maximum Physical Activity in White Rats (Rattus Norvegicus) - Togatorop, Wilson H. S.; Harahap, Novita Sari (Universitas Muhammadiyah Sumatera Utara, 2021)
The effect of physical activity on biological functions can be either positive or negative influences. Severe physical activity can increase oxygen consumption by 100-200 times compared to resting conditions. Increased use of oxygen, especially by muscle contracting, causes an increase in the number of free radicals. This study aims to determine the effect of maximum physical activity on cholesterol levels in white rats. The research design was used an experimental study with a post-test and control group design. Subjects were male white rats (Rattus Norvegicus), 20 of them were 3-4 months old, body weight was 180-200 grams. Subjects were divided into 2 groups randomly, each group consisted of 10 white rats, namely the control group: not given maximum physical activity; group treated: given maximum physical activity in the form of swimming until almost submerged. The results showed a significant increase in cholesterol levels (p=0.035; p0.05) in the treatment group, namely the group that was given maximum physical activity in the form of swimming to almost drowning, compared to the control group, namely the group that did not swim. The study concluded that there was an effect of maximum physical activity on blood cholesterol levels in white rats (Rattus Norvegicus).